The Role of the Sarungan Task Force on Bullying Prevention in Santri - Retno Windarwati; Dartim Dartim (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
Bullying in Islamic boarding schools is still a serious problem that affects the mental well-being and learning comfort of students. Al-Muayyad Islamic Boarding School Surakarta formed the Sarungan Task Force (Santri Anti Bullying and Violence) to prevent and handle bullying. This study aims to analyze the role of the Sarungan Task Force in preventing and handling bullying in the Islamic boarding school environment. The study used a descriptive qualitative method with a case study approach. The study subjects included the Sarungan Task Force members, senior students, junior students, and Islamic boarding school administrators. Data collection techniques used participatory observation, in-depth interviews, and documentation. Data analysis used thematic analysis with triangulation of sources and techniques. The Sarungan Task Force reduced bullying cases from weekly reports to only two monthly reports. This program applies an educational approach through educational sanctions, counseling, mediation, and routine socialization. The most common forms of bullying are verbal and social, with a culture of seniority still visible, although in a milder form. The Sarungan Task Force has proven effective in suppressing bullying cases through a comprehensive approach that combines Islamic values ??and positive discipline. However, continuous reinforcement is still required to overcome the challenges of seniority culture and understand the boundaries between joking and bullying